The Role and Efficacy of Rifaximin in the Treatment of Irritable Bowel Syndrome - Based on current research in 2026 - Jabrzyk, Martyna; Fahim, Knieszko; Franaszek, Jakub; Herchi, Nadia; Jarczyńska, Patrycja; Kijowski, Wojciech; Klusek, Mateusz; Michalak, Karolina; Przybył, Maciej; Celoch, Kornel (Quality in Sport, 2026)
Introduction In 2026, irritable bowel syndrome (IBS) was recognized as a complex disorder of the gut-brain axis involving microinflammation, increased intestinal permeability and dysbiosis. Modern therapy is moving away from symptom relief to modulation of the microflora. Rifaximin, due to its minimal absorption and solubility in bile salts, is the first-line treatment for IBS-D. As a eubiotic, it reduces pathogens, supports beneficial microflora and strengthens the intestinal barrier thanks to tight junction proteins. Clinical data shows that it is safe for high-risk groups, such as cardiac patients taking anticoagulants and antiplatelet drugs, due to the absence of systemic interactions. Aim of the study Summary of the status of rifaximin alfa in IBS in 2026, focusing on its molecular mechanisms, impact on the gut-brain axis, and safety in patient populations with comorbidities. Materials and methods A systematic review of PubMed (last 10 years) was conducted using the keywords: „IBS”, „RIFAXIMIN”, „TREATMENT”. Pediatric studies were excluded. Conclusions Rifaximin is the first choice for treating IBS-D, surpassing both traditional methods and low-FODMAP diets. Its advantages include regeneration of the intestinal barrier, physiological modulation of bile acids and reduction of gastrointestinal-specific anxiety (GSA). With a safety profile comparable to placebo and no significant drug interactions (especially with antiplatelet/anticoagulants), it provides stable disease control and improved quality of life.